Self-assembly of a silylated steroid-based organogelator and its use as template for the in situ sol-gel polymerization of tetraethyl orthosilicate - Edelsztein, Valeria Carolina (2010)
In this paper we report the synthesis of a new steroid-based low-molecular weight organogelator, the analysis of the self-assembled fibrilar network (SAFIN) and its use as template for the preparation of SiO2 nanotubes. This novel steroidal organogelator has a unique structure among the well known family of steroid-based organogelators, the most important characteristic of this molecule is the presence of a silyl ether group at C-3 together with a 6β,19-oxo bridge. It was capable to gelate hydrocarbons and tetraethyl orthosilicate at very low concentrations (<1 wt %). An insight into the aggregation mechanism is provided revealing that complementary interaction between an α-oriented hydrogen bond donor and a β-oriented acceptor on the steroid skeleton is the driving force for the primary 1D self-assembly. The SAFIN was successfully used as template to grow silica nanotubes (external diameter: 40-60 nm, internal diameter: 7 nm and several micrometers length) through a catalyst-free in situ co-assembly polymerization process. Hydrogen bond or electrostatic interactions between the anionic silicate intermediate species and the SAFIN are proposed to be the driving force for templating.